2019
DOI: 10.3892/ijmm.2019.4278
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-592 suppresses the malignant phenotypes of thyroid cancer by regulating lncRNA NEAT1 and downregulating NOVA1

Abstract: Numerous studies have demonstrated that various microRNAs (miRs) are aberrantly expressed in thyroid cancer and play critical roles in thyroid cancer malignancy. The aberrant expression of miR-592 has frequently been reported in multiple human cancer types; however, its expression profile and functions in thyroid cancer remain poorly understood. Reverse transcription-quantitative polymerase chain reaction was carried out to determine the expression profile of miR-592 in thyroid cancer tissues and cell lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Nuclear enriched abundant transcript 1 (NEAT1) is a classic lncRNA that is specifically located in paraspeckles and functions as an essential structural determinant by interacting with members of the Drosophila behavior human splicing (DBHS) family of proteins (32)(33)(34)(35). Recently, emerging evidence has suggested that NEAT1 is intricately associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear enriched abundant transcript 1 (NEAT1) is a classic lncRNA that is specifically located in paraspeckles and functions as an essential structural determinant by interacting with members of the Drosophila behavior human splicing (DBHS) family of proteins (32)(33)(34)(35). Recently, emerging evidence has suggested that NEAT1 is intricately associated with inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer is a common malignant tumor of the endocrine system, its incidence keeps increasing year by year driven by the change of social environment (1). However, due to the latent onset of thyroid cancer, many patients are diagnosed with metastasis, hazarding the prognosis of patients (2,3). The fact that the current diagnosis and treatment of thyroid cancer offer few options results in unsatisfactory therapeutic effect for many patients (4).…”
Section: Introductionmentioning
confidence: 99%
“… 42 MiRNA-592 suppresses thyroid cancer development by downregulating NOVA1 and controlling lncRNA NEAT1. 43 MiRNA-15 mediates thyroid cancer invasion, migration, and proliferation by regulating Bcl-2. 44 It has been identified that miR-422a participates in thyroid cancer modulation.…”
Section: Discussionmentioning
confidence: 99%